Transformasi Wali Mujbir dalam Hukum Keluarga Islam Indonesia: Perspektif Uṣūl Fikih dan Maqāṣid al-Syarī‘ah - Darliswanto Darliswanto; Syahril Anwar; Zulikrami Zulikrami (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
This study examines the transformation of the concept of wali mujbir in Indonesian Islamic family law through the perspectives of uṣūl al-fiqh and maqāṣid al-sharī‘ah. The research aims to analyze the normative construction of wali mujbir in classical Islamic jurisprudence, explain its transformation in Indonesian Islamic family law, and assess the legitimacy of such transformation. This study employs a library research method using normative Islamic legal and conceptual approaches through the examination of classical fiqh literature, prophetic traditions (hadith), family law regulations, and relevant academic sources. The findings indicate that wali mujbir constitutes an ijtihād-based legal institution grounded in ẓannī al-dalālah evidence, thereby allowing reinterpretation in response to social change and public benefit. Indonesian Islamic family law maintains the institution of guardianship (wali nikah) while reconstructing its authority from a wilāyat al-ijbār model toward an administrative-normative function emphasizing spousal consent, legal protection, and procedural legitimacy. This transformation gains legitimacy through the concepts of taghayyur al-aḥkām bi taghayyur al-zamān, maṣlaḥah, and siyāsah shar‘iyyah, and aligns with the objectives of maqāṣid al-sharī‘ah in protecting human dignity, family welfare, and preventing harm.